2016
DOI: 10.1101/071415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification ofKlebsiellacapsule synthesis loci from whole genome data

Abstract: Klebsiella pneumoniae is a growing cause of healthcare-associated infections for which multi-drug resistance is a concern. Its polysaccharide capsule is a major virulence determinant and epidemiological marker. However, little is known about capsule epidemiology since serological typing is not widely accessible and many isolates are serologically non-typeable. Molecular typing techniques provide useful insights, but existing methods fail to take full advantage of the information in whole genome sequences. We i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 68 publications
1
17
1
Order By: Relevance
“…Previous work also demonstrated that vaccines (either monovalent or polyvalent) can protect against multiple (as many as 71) Klebsiella capsule types (35,42). The majority of ST258 clinical isolates in the United States and many other regions of the world are composed of one of only two capsule polysaccharide types (cps-1 or cps-2) (10,13,15,17). Therefore, as a starting point, a vaccine that targets the most prominent strains of carbapenem-resistant K. pneumoniae need be effective only against cps-1 and cps-2 strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work also demonstrated that vaccines (either monovalent or polyvalent) can protect against multiple (as many as 71) Klebsiella capsule types (35,42). The majority of ST258 clinical isolates in the United States and many other regions of the world are composed of one of only two capsule polysaccharide types (cps-1 or cps-2) (10,13,15,17). Therefore, as a starting point, a vaccine that targets the most prominent strains of carbapenem-resistant K. pneumoniae need be effective only against cps-1 and cps-2 strains.…”
Section: Resultsmentioning
confidence: 99%
“…Recent genome analyses indicate that the two major clades of ST258 encode different capsule polysaccharide (CPS) types by gene clusters known as cps-1 and cps-2 (12)(13)(14). These two capsule types remain predominant among ST258 clinical isolates worldwide, and cps-2 isolates are more abundant than cps-1 isolates in many geographic regions (10,13,(15)(16)(17). The contribution of CPS to the success of ST258 outside antibiotic resistance remains incompletely determined.…”
mentioning
confidence: 99%
“…A detailed description of the algorithm is reported in the Supplementary Note S1. To develop an HRM-based protocol for K. pneumoniae typing, we focused on the seven MLST genes and on the hypervariable capsular gene wzi 23 . The HRM primer pairs for five out of the seven K. pneumoniae MLST genes were already available in literature 7 (infB, mdh, phoE, rpoB and two pairs on tonB).…”
Section: Methodsmentioning
confidence: 99%
“…Reads were trimmed using Trimmomatic (10) and were then assembled to 125 contigs (70 were Ն1,000 bp in length) with a 56.79% GC content using the SPAdes program (11). The wzi gene allele, which represents the capsular variation, of strain WCHKP020034 was 50, corresponding to several K types, i.e., K15, K17, K50, K51, and K52, with K15 being the best match predicted using Kaptive (12). None of the K types were K1, K2, or K5, which are proposed as the hypervirulent members of K. pneumoniae.…”
mentioning
confidence: 99%
“…The filtered SNPs were then used as input for inferring a phylogenetic tree using RAxML (16) with the GTRGAMMA model and 1,000 bootstraps. Antimicrobial resistance genes in these genomes were identified using ABRicate (https://github.com/ tseemann/abricate) to query the ResFinder database at the Center for Genomic Epidemiology (http://genomicepidemiology.org/), and the wzi gene allele was predicted using Kaptive (12). Five strains carrying bla NDM-7 , a point mutant of bla NDM-1 , were recovered in 2013 in the Philippines and belonged to a single cluster.…”
mentioning
confidence: 99%